Prosedur Clearance In dan Clearance Out TugBoat – Tongkang PT. Patria Maritime Lines Oleh PT. Barito Samudra Sejahtera Cabang Banjarmasin - Laily Nurfiana Wardhani; Nurul Azizah (International Forum of Researchers and Lecturers, 2023)
Indonesia is one of the world's largest coal exporters. One of the means of sea transportation to transport coal is tugboats and barges. PT. Patria Maritime Lines is a shipping company that focuses its services on the transportation of coal and other energy from mining concessions and various commodities. PT. Barito Samudra Sejahtera is a company that provides ship agency services which currently supports the ship operations of PT. Patria Maritime Lines. The duty of the shipping company, PT. Barito Samudera Sejahtera, namely taking care of Clearance In and Clearance Out documents for tugboats and barges that will dock at the Unloading Port and unload or load goods. This study aims to determine the procedures and supporting documents required for Clearance In and Clearance Out. This study uses observation, interviews, documentation, and literature study as qualitative methods. It was found in this research that As an agent, PT. Barito Samudra Sejahtera must know the Clearance In and Clearance Out procedures and what documents can be returned, especially those on the ship or tugboats and accompanying barges.